Kerangka Penguatan Sistem Hukum untuk Menghentikan Kekerasan Berbasis Gender Online di Indonesia - Ahmad Habib Al Fikry (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2022)
Today, online gender-based violent crime is a global crisis phenomenon. This crime that takes human rights is spreading like cancer cells because it is in line with the development of the world which is closely related to advances in information and communication technology. This condition then places humans to have an attachment to these entities in everyday life. The coherence is the increasing incidence of these crimes that have transcended the scale of the crisis through the dimensions of cyberspace that give rise to complexity. Therefore, it is necessary to strengthen the legal system that focuses on victims of online gender-based violence. The aims of this paper are: (i) to explain online gender-based violence as a crime in cyberspace; and (ii) describe the framework for strengthening the legal system to combat online gender-based violence in Indonesia. The author uses a normative juridical writing method. The results show that: (i) online gender-based violence is part of crime in cyberspace; and (ii) the framework for strengthening the legal system is carried out through a 3-point approach, including aspects of the system, legal culture, and access to justice. These three aspects are carried out as a form of preventive and repressive efforts so that online gender-based violent crime law enforcement can work effectively. In addition to empowering women and reducing the number of crime cases, through this comprehensive framework, crime victims can obtain legal protection so that their rights can be fulfilled.